Sistem Informasi Pengendalian Piutang dengan Metode Average Collection Period pada Koperasi Dahlia Cepiring - Kamto Sudibyo, sukemi; Wahyuning, Sri; Isma, Syahadah (Jurnal Ilmiah Sistem Informasi, 2023)
The Dahlia Cepiring Cooperative operates in the savings and loans sector. The admin records each customer's loan in one folder, then the admin inputs the data into Microsoft Excel. The process of granting KSP Dahlia Cepiring loans is fast and easy, submitting collateral and the requirements for KTP, STNK and KK so that the amount of receivables increases greatly, which of course can create a risk of difficulties in managing and reporting receivables. The result of this research is the implementation of a receivables control information system at the Dahlia Cepiring cooperative to manage, control receivables and produce receivables reports using the Average Collection Period method which is able to minimize losses on receivables and speed up the movement of receivables into cash.